Real-world outcomes of Selexipag for treatment of pulmonary hypertension in an Asian population. (25th January 2023) - Loo, G; Yap, J; Hon, J S; Ismail, A; Lim, C L; Sumanthy, P; Ruan, W; Sewa, D W; Phua, G C; Ng, S A; Hong, C; Low, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Selexipag is an oral selective prostacyclin IP receptor agonist indicated for treatment of pulmonary arterial hypertension (PAH). Data on its real-world safety and efficacy in Asians is lacking. Purpose: We sought to evaluate the clinical characteristics, treatment regimens and outcomes of patients initiated on selexipag in a tertiary cardiac centre in Asia. Methods: This was a retrospective study on all patients initiated on selexipag from January 2017 to December 2020. Baseline and follow up characteristics including demographics, functional status and clinical data were collected. Clinical outcomes evaluated included hospitalisation for PH related complications and all-cause mortality. Patients were risk stratified using the COMPERA 2.0 risk scores. Results: A total of 36 PAH patients were treated with selexipag. At baseline, most patients were WHO functional class II or III (36.4% and 51.5% respectively), with a NT-proBNP of 1335 pg/ml (557 – 2918) and 6 minute walk test (6MWT) duration of 327.5 ±126.4 meters. Selexipag was initiated at 200mcg twice daily dosage for all except one patient (started at 200mcg once daily) and the maximum tolerated dose ranged from 200mcg twice daily to 1400mcg twice daily, with majority tolerating up to a dose of 600mcg twice daily (58.3%). Side effects were reported in 23 patients (63.9%), of which headache (27.8%), diarrhea (30.6%) or musculoskeletal symptoms (27.8%) were predominant. After a median follow up duration of 25.9 ± 23.1 months, selexipag was stopped in 20 patients (55.6%), of which eight patients were due to PAH progression requiring alternative therapy, and 12 patients due to side effects from selexipag. At baseline, patients were classified into low (8.3%), intermediate-low (30.6%), intermediate-high (33.3%) and high risk (27.8%) respectively. Patients who continued on selexipag at follow up showed no change (46.2%), improvement (15.4%) and deterioration (38.5%) in risk score. In the overall cohort of 36 patients, majority (75%) had at least one hospitalisation for PAH related complications and 15 patients (41.7%) demised. Conclusion: In this real-world study, while selexipag was associated with a stable or improved PAH risk scores in majority of patients, there was a subset of patients with disease progression or intolerance to the medication. Further studies are warranted to identify patients who will benefit most from this therapy. Table 1. Patient Characteristics